The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1001/jama.2014.16425
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Life Expectancy in a Scottish Cohort With Type 1 Diabetes, 2008-2010

Abstract: Estimated life expectancy for patients with type 1 diabetes in Scotland based on data from 2008 through 2010 indicated an estimated loss of life expectancy at age 20 years of approximately 11 years for men and 13 years for women compared with the general population without type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
344
3
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(376 citation statements)
references
References 15 publications
14
344
3
15
Order By: Relevance
“…Interestingly, all‐cause mortality, and the combined outcome (stroke and death), were only slightly increased in type 2 diabetes patients compared to patients without diabetes. Others have demonstrated an increased risk of death in type 1 diabetes patients 27, 28. In a nationwide study, based on data from the Swedish National Diabetes Register, it was found that type 1 diabetes individuals, even at optimal glycemic control, had twice as high a risk of death, predominantly from CVD, compared to matched controls from the general population 27.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all‐cause mortality, and the combined outcome (stroke and death), were only slightly increased in type 2 diabetes patients compared to patients without diabetes. Others have demonstrated an increased risk of death in type 1 diabetes patients 27, 28. In a nationwide study, based on data from the Swedish National Diabetes Register, it was found that type 1 diabetes individuals, even at optimal glycemic control, had twice as high a risk of death, predominantly from CVD, compared to matched controls from the general population 27.…”
Section: Discussionmentioning
confidence: 99%
“…3 T1DM can occur at any age, but is usually diagnosed in children and adolescents 1 and its incidence has been rising steadily in developed countries since the 1950s. 4 It is caused by the absolute lack of insulin production due to autoimmune destruction of the insulin-producing beta cells of the pancreas.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…A newly published systematic review assessing mortality in type 1 diabetes documented less marked excess mortality in more recent studies [19]. A recent Scottish study estimated a lower life expectancy compared with that of the general population [20]. Long-term follow-up of patients with type 1 diabetes in the Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC) showed a modestly lower mortality rate in those initially receiving intensive therapy compared with those receiving conventional therapy [21], and a Swedish register study reported that the risk of mortality increased with increasing HbA 1c [22].…”
Section: Introductionmentioning
confidence: 99%